Roadmap to implement Enterprise Content Management in a Manufacturing industry: - (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Purpose The purpose of this document is to outline the roadmap which will help an organization to take adecision to implement Enterprise Content Management.Designmethodologyapproach The paper presents and analyses a longitudinal study of an ECM project.Findings The findings of the paper include a definition of a process model for ECM implementation in amanufacturing industry and SMEs.Research limitationsimplications An overview of ECM system implementation in manufacturingindustry, this paper provides an implementation roadmapin a manufacturing industry.Practical implications This paper is application for those organization who are planning to implementECM.Originalityvalue The paper is an attempttowardECM implementation guideline. In fact, the article is casestudy of ECM implementation in manufacturing industry